UPAYA MENINGKATKAN KEAKTIFAN PESERTA DIDIK KELAS V DALAM PEMBELAJARAN BAHASA INGGRIS DI SDIT USWATUN HASANAH BOGOR MELALUI METODE TEAM GAMES TOURNAMENT - Siti Nurjanah; Luh Ade Yuanita Andriani (Jurnal Cendekia Ihya, 2023)
Learning English is learning that aims to develop the ability to communicate in English both in spoken and written form.. However, unfortunately there are still many students who are not confident to practice pronunciation in English. In addition, some students have not been able to understand the meaning of English vocabulary. Therefore, to overcome this problem the researcher wants to use the Team Games Tournament (TGT) learning model for the activeness of students in English class V lessons at the Integrated Islamic Elementary School Uswatun Hasanah Bogor in the even semester of the 2022/2023 academic year. Thus, researchers will provide solutions to create an interesting classroom atmosphere, which can lead to activeness, interest and enthusiasm for learning, as well as improve student learning outcomes, especially in English lessons through the Team Games Tournament (TGT) cooperative learning model. The results of the research show an increase in the learning activity of students in learning English through the cooperative learning model of the Team Games Tournament (TGT) type. In cycle I the Team Games Tournament (TGT) learning model can increase activity learners. With the acquisition of cycle I on very good criteria of 46% (5 people), good criteria of 18% (2 people), pretty good criteria of 18% (2 people), unfavorable criteria of 9% (1 person), and 1 students were absent with a percentage of 9%. Whereas in cycle II there was an increase in the acquisition of learning activeness of students with very good criteria of 81.9% (9 people), good criteria of 9.1% (1 person), good enough and not good criteria of 0% (none) , and the absence of students 9.1% (1 person). The Team Games Tournament (TGT) learning model carried out can maintain student learning outcomes thoroughly, with the acquisition of cycle I and cycle II of completeness of 90.1%.